1998
DOI: 10.1175/1520-0477(1998)079<2527:acodpm>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

A Climatology of Derecho-Producing Mesoscale Convective Systemsin the Central and Eastern United States, 1986–95. Part I: Temporal and Spatial Distribution

Abstract: In 1888, Iowa weather researcher Gustavus Hinrichs gave widespread convectively induced windstorms the name "derecho". Refinements to this definition have evolved after numerous investigations of these systems; however, to date, a derecho climatology has not been conducted. This investigation examines spatial and temporal aspects of derechos and their associated mesoscale convective systems that occurred from 1986 to 1995. The spatial distribution of derechos revealed four activity corridors during the summer,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
84
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(95 citation statements)
references
References 14 publications
10
84
1
Order By: Relevance
“…As such, those that formed most commonly entered the northern part of the state and progressed towards the southeast through central and eastern Oklahoma. Further, these storm occurrences are consistent with 'southward-burst derecho-producing mesoscale convective systems' identified by Bentley and Mote (1998) as well as the secondary high frequency axis of northwesterly flow severe weather events identified by Johns (1982). Finally, throughout the final 3 months of the year, squall lines decreased in number and were confined mainly to central and eastern…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…As such, those that formed most commonly entered the northern part of the state and progressed towards the southeast through central and eastern Oklahoma. Further, these storm occurrences are consistent with 'southward-burst derecho-producing mesoscale convective systems' identified by Bentley and Mote (1998) as well as the secondary high frequency axis of northwesterly flow severe weather events identified by Johns (1982). Finally, throughout the final 3 months of the year, squall lines decreased in number and were confined mainly to central and eastern…”
Section: Resultssupporting
confidence: 77%
“…Subsequent definitions of other linear convective storms have been applied to more extreme events such as derechos (Johns and Hirt, 1987) and bow echoes (Fujita, 1978). Using set derecho definitions, studies such as Bentley and Mote (1998), Bentley and Sparks (2003), and Coniglio and Stensrud (2004) have quantified the frequencies of such storms across the United States and identified noticeable shifts in high-frequency regions stretching from the Great Lakes region through the Southern Plains during the warm season (May to August) to the lower Mississippi Valley during the cool season (September to April). Burke and Schultz (2004) focussed on the climatologies of bow echoes during the typically lower-frequency cool season and found similar spatial patterns as revealed in several derecho studies.…”
Section: Introductionmentioning
confidence: 99%
“…their section 2). Later studies by Bentley and Mote (1998), Evans and Doswell (2001), Bentley and Sparks (2003), and Coniglio and Stensrud (2004) have utilized differing criteria to define derechos. United States derechos have been documented in the literature since the early 1980s (e.g., Johns and Hirt 1983); only recently have enough events been documented over a sufficient period to begin to analyze the climatology of these windstorms.…”
Section: Doi: 101175/bams-86-11-1577mentioning
confidence: 99%
“…Johns and Hirt (1987) were the first to present a climatology of these events for the warm seasons from 1980 to 1983. Bentley and Mote (1998) and Bentley and Sparks (2003) recently analyzed the years 1986-2000, providing the basis for a 15-yr derecho climatology, including both cool-and warm-season events. These studies identified the tendency for derechos to occur in specific seasonal corridors in the eastern two-thirds of the United States.…”
Section: Doi: 101175/bams-86-11-1577mentioning
confidence: 99%
“…These rains were believed to have increased evapotranspiration rates from actively growing Midwestern corn (Zea mays L.) and soybean (Glycine max L.) crops. Studies that examined conditions prior to the development of Midwest mesoscale convective systems (MCSs) postulated that the primary source for low-level moisture during weak-flow (anticyclonic) situations was evapotranspiration from crops, not moisture advection from the Gulf of Mexico (Chang & Wetzel 1991, Bentley & Mote 1998, Changnon & Kunkel 1999. The possibility exists that changes in agricultural practices relating to corn and soybean production have also had an influence on the amount of evapotranspiration from an acre of Midwestern farm land.…”
Section: Introductionmentioning
confidence: 99%